Rekonstruksi Hukum Pengaturan Rencana Tata Ruang Wilayah Provinsi Kalimantan Tengah Berbasis Keberlanjutan Lingkungan - Laksminarti Laksminarti (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2019)
The research aims to obtain an overview of the legal reconstruction of the regional Spatial Plan of central Kalimantan province-based environmental sustainability. The policy and strategy of spatial and regional development are required to answer the issues or development problems that develop today. The issues include the occurrence of conflicts of interest between sectors, such as mining, environment, forestry, regional infrastructure and so on. Spatial planning does not work optimally to synchronize various sector plans and programs. The occurrence of space utilization deviation from the provisions and norms that should be enforced due to policy inconsistency of spatial plans and weaknesses in development control. The occurrence of a discrepancy between the legal provisions governing the spatial plan with the facts occurring in the field. This type of research is the research of normative law which is also commonly referred to as the type of doctrinal law research. According to Wignoyosoebroto this type of research is a study of the laws that are conceptualized and developed based on the doctrines adopted by the conceptualizing and or the developers. The results showed that the overlap of legislation between state institutions poses confusion for it is required once the renewal of law between state agencies so as not to happen overlap or Inconsistency between the laws and regulations of the other legislation.